Hubungan Kebiasaan Konsumsi Seng dan Zat Besi dengan Kejadian Stunting pada Anak di SD Negeri No. 117504 Aek Pamingke Labuhan Batu Utara Tahun 2017 - Theresya Vyrena Simorangkir; Ernawati Nasution; Albiner Siagian (Gizi, Kesehatan Reproduksi dan Epidemiologi, 2018)
Stunting is a failure to achieve optimal growth experienced since ancient times thus causing the achievement of growth that is not perfect. So this research aims to determine the correlation between zinc and iron consumption habit and stunting insidence in children of elementary school in SD Negeri No. 117504 Aek Pamingke Labuhan Batu Utara. Based on the initial survey established found 42% of students sustain stunting and students with the consumption of zinc and iron are in the good chategory only in the amount of 9%. This type of research is quantitative with cross sectional design and sample is 75 students. The data about student’s characteristic (age and sex), zinc and iron consumption habit obtained by using qustionarre, and stunting case data obtained by using anthropometry measurement. Analysis correlation between independent variabel and dependent variabel using chi square test. Result showed the percentage proportion of stunting students is 44% and non-stunting students is 56%. From bivariate analysis result between zinc consumption habit with stunting incidence showed p value=0,022 and RP value=4,13. Result analysis between iron cinsumption with stunting incidence showed p value=0,006 and RP value=4,421. So can be observed meaningful correlation between zinc and iron consumption habit with incidence of stunting in children of the primary school. Then from the result can be concluded that consumption habit of zinc and iron relate to the stunting incidence in SD Negeri No. 117504 Aek Pamingke Labuhan Batu Utara. This result suggested to the school and parents in order to pay more attention to children food consumption, both at school and home, to reduce the risk of stunting in children. Keywords: Student, Stunting Insidence, Zinc and Iron Consumption.